Analysis of Marine Water Quality to Facilitate Management in Support of Mangrove Conservation in Kayo Batu Village, Jayapura - Maturbongs, Gaviota J.T.; Nainggolan, Hotnida; Rumawak, Sarah A. (INSPIRETECH GLOBAL INSIGHT, 2025)
Purpose of the study: this investigation aimed to assess the quality of marine water by analyzing a range of physico-chemical parameters, such as pH, dissolved oxygen (DO), total dissolved solids (TDS), dissolved hydrogen ions (DHL), salinity, and temperature, in addition to determining its importance in promoting mangrove conservation initiatives. Materials and methods: A quantitative approach was used by measuring water quality at eight sampling points during morning and afternoon sessions, combined with a questionnaire distributed to 88 respondents to capture community perceptions of environmental changes. Results: The results indicate that marine water quality in Kayo Batu Village is classified as lightly polluted but remains within the permissible threshold according to the Minister of Environment Decree No. 51 of 2004. Some parameters, such as DO and pH, slightly exceed the optimal range for healthy mangrove ecosystems. Community perceptions reveal concerns about declining water quality due to poor sanitation and domestic pollution. Therefore, a mangrove conservation strategy based on adaptive and participatory approaches is necessary, particularly through the control of pollution sources, environmental education, and improved sanitation infrastructure. Conclusions: The findings of this study are expected to serve as a scientific basis for policy formulation to sustainably preserve the coastal ecosystem.